F-layer critical frequency determination from ionospheric Alfven resonance observations - Koloskov, A. V.; Baru, N. A. (Ukrainian Antarctic Journal, 2012)
The parameters of the ionospheric Alfven (IAR) and Schumann (SR) resonances are determined by the intensity of their source (global thunderstorm activity) and properties of the propagation medium (the ionosphere and magnetosphere of the Earth). Our observations and results of other authors show that the SR depends primarily on the global parameters of the source and propagation medium. Otherwise the IAR features are mainly determined by local characteristics of the near-earth plasma. The latter circumstance was the basis for the authors to analyze the possibility of diagnostics of the local ionosphere using the IAR data. ELF recordings, obtained at the Ukrainian Antarctic Station (UAS) and low-frequency observatory IRA NAS Ukraine (LFO) were used for the analysis. The presence of long-term data sets obtained at the points with a spatial spacing of about 15 thousand kilometers, allowed us to study the basic seasonal and diurnal behavior of the eigenfrequencies and “observability”of IAR, as well as to investigate the dependence of these parameters from the site position. IAR characteristics were compared with synchronous data of the ionospheric sounding and the total electron content (TEC) over the observation points. A joint analysis of data showed that plasma parameters at the height of the ionosphere F-region have a major impact on the variation of eigenfrequencies of IAR. The article describes a phenomenological model and proposes the technique of estimation of the magnitude of the critical frequency of F layer - F2f0 based on the calculation of frequency interval between the IAR peaks -<span style="display: inline !important; float: none; background-color: #ffffff; color: #222222; font-family: arial,sans-serif; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Δf. The reliability of this technique is confirmed comparing the reconstructed values F2f0 with the vertical sounding data obtained at UAS.